2020
DOI: 10.3390/ijerph17249532
|View full text |Cite
|
Sign up to set email alerts
|

Current Psychological Distress, Post-traumatic Stress, and Radiation Health Anxiety Remain High for Those Who Have Rebuilt Permanent Homes Following the Fukushima Nuclear Disaster

Abstract: Objective: The Fukushima Daiichi nuclear disaster in 2011 produced psychological reactions among evacuees. Despite the harsh situation, subsequently, there has been gradual progress in reconstruction, with more than half of the evacuees returning after the evacuation. Our hypothesis is that evacuee mental health will now be better due to new stable living conditions. This study aims to clarify the statuses of psychological distress, post-traumatic stress, and radiation health anxiety among evacuees who have re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
0
11
1
Order By: Relevance
“…The internal exposure dose of 99.986% of approximately 184,000 residents was less than one mSv [30]. A study showed that radiation-related health concerns among evacuees were still high in 2020 compared to those who were not evacuated [31]. Another study found that radiation-related anxiety among Fukushima residents was resolved over time between 2012 and 2015.…”
Section: Discussionmentioning
confidence: 99%
“…The internal exposure dose of 99.986% of approximately 184,000 residents was less than one mSv [30]. A study showed that radiation-related health concerns among evacuees were still high in 2020 compared to those who were not evacuated [31]. Another study found that radiation-related anxiety among Fukushima residents was resolved over time between 2012 and 2015.…”
Section: Discussionmentioning
confidence: 99%
“…F also increased, which can reflect the mental health status of returnees [ 14 ]. According to Orui et al, many evacuees still have high levels of psychological distress, post-traumatic stress, and health anxiety due to radiation, similar to those who remain evacuated even if their living environment improves [ 15 ]. Maeda and Oe also reported serious mental health problems in evacuees, including an increase in disaster-related suicides, despite a gradual decline in anxiety and depressive symptoms [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…[35]. Furthermore, our previous study reported that the levels of psychological distress, post-traumatic stress, and radiation health anxiety were found to still be high among residents who had rebuilt permanent homes after the evacuation, with significant differences compared with those who did not evacuate [3]. Moreover, higher risk perceptions of radiation exposure after the nuclear accident were associated with later post-traumatic stress symptoms [36].…”
Section: Relationship Between Psychological Distress and Post-traumatic Stress Among Those Who Have Continuing/emerging Strong Radiation mentioning
confidence: 95%
“…The nuclear accident at the Fukushima Daiichi nuclear power plant caused multiple public health problems, one of which was increased anxiety and mental health issues 2 of 16 due to perceived risk among the evacuees and residents of Fukushima. Our previous study reported that the current status of psychological distress, post-traumatic stress, and radiation health anxiety remained high for those rebuilding their permanent homes after evacuation orders had been lifted [3]. However, it is necessary to indicate a clear interaction among high psychological distress, continuing strong radiation anxiety, and post-traumatic stress.…”
Section: Introductionmentioning
confidence: 98%